Ego Death: The Loss of ‘Subjective Self-identity’ in Ionesco’s Rhinoceros - Bakhtiar S. Hama (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
In Jungian Psychology, Ego death is known as psychic death. It simply means that the person improves his/her past life and makes radical changes in it as if he was born again; he goes from one stage to another to start life anew. This transformation of the psych is crucial for human beings to rebuild their lives if the ego death is positive. In this case, mind will become a tabula rasa and the persons can design a beautiful future on it. Unfortunately, the metamorphosis or the ego death in Ionesco’s Rhinoceros is mostly negative. The characters, except Berenger, become rhinoceroses; they lose their subjective identity one after another. Their change is not to return to their pure origin as human beings but to become a dangerous beast. The characters know the conversion is epidemic; yet they do not resist it. On the contrary, they go out and some of them happily receive it, like Daisy. They admire their new form and are happy with it as if being an animal was better than being a man in the current status. This study shows that humanity is in danger and also clarifies that human beings are fed up with being humans. They take new forms and risk man values and features hoping that they can find a meaning for their lives, but they fail. Almost all the characters, cattle-like, follow the bad norm, but Berenger refuses to surrender and embrace the transformation since he believes that it is better to change the essence not the form. He saves his self-identity while others are losing theirs, though it is very hard.